Discovery of a morphologically and genetically distinct population of Black‐tailed Godwits in the East Asian‐Australasian Flyway. (21st October 2020) - Zhu, Bing‐Run; Verkuil, Yvonne I.; Conklin, Jesse R.; Yang, Ailin; Lei, Weipan; Alves, José A.; Hassell, Chris J.; Dorofeev, Dmitry; Zhang, Zhengwang; Piersma, Theunis
Abstract : Occurring across Eurasia, the Black‐tailed Godwit Limosa limosa has three recognized subspecies, melanuroides, limosa and islandica from east to west, respectively. With the smallest body size, melanuroides has been considered the only subspecies in the East Asian‐Australasian Flyway. Yet, observations along the Chinese coast indicated the presence of distinctively large individuals. Here we compared the morphometrics of these larger birds captured in northern Bohai Bay, China, with those of the three known subspecies and explore the genetic population structuring of Black‐tailed Godwits based on the control region of the mitochondrial genome (mtDNA). We found that the Bohai Godwits were indeed significantly larger than melanuroides, resembling limosa more than islandica, but with relatively longer bills than islandica . The level of genetic differentiation between Bohai Godwits and the three recognized subspecies was of similar magnitude to the differentiation among previously recognized subspecies. Based on these segregating morphological and genetic characteristics, we propose that these birds belong to a distinct population, which may be treated and described as a new subspecies.